Low-dose ramosetron accelerates gastric emptying in the early phase: A crossover study in healthy volunteers using a continuous real-time 13C breath test (BreathID System) - Inoue, Sho; Sakamoto, Yasunari; Sekino, Yusuke; Nonaka, Takashi; Iida, Hiroshi; Endo, Hiroki; Koide, Tomoko; Takahashi, Hirokazu; Maeda, Shin; Nakajima, Atsushi; Gotoh, Eiji; Inamori, Masahiko (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: The aim of this study was to determine the correlation between low-dose ramosetron pre-treatment and gastric emptying using a novel, non-invasive technique for measuring gastric emptying, namely, the continuous real-time 13C breath test (BreathID system: Exalenz Bioscience Ltd., Israel). Materials and Methods: Twelve healthy male volunteers participated in this randomized two-way crossover study. The subjects fasted overnight and were randomly assigned to receive the test meal (200 kcal per 200 mL) after an hour pre-treatment with 5 µg ramosetron or the test meal alone. Gastric emptying was monitored for 4 hours after administration of the test meal with the 13C-acetic acid breath test performed continuously using the BreathID system. Using Oridion Research Software (β version), T 1/2, T lag, GEC and the regression-estimated constants (β and κ) were calculated. The differences in the parameters measured at two time-points were analyzed using Wilcoxon’s signed-rank test. Results: There was a significant difference in the calculated parameter β. No significant differences in the calculated parameters T 1/2, T lag, GEC or κ were observed between the test meal with ramosetron group and the test meal alone group. Conclusion: This study showed that ramosetron pre-treatment enhances the early gastric emptying of liquid nutrients.